INFORMASI PENDIDIKAN DENGAN PORTAL LAYANAN PUBLIK NASIONAL - Mustika, Rieka (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2010)
This article aims to give input to the Government in presenting educational information services. National Public Service Portal needed because of expected to bridge the interests of the community who wants one container of e-government facilities that are integrated, as well as in the central and local governments that have implemented e-government facilities in their respective institution to be well integrated in one this container. In the end it takes some websites to fill the service classification in this public service portal. Education is one of public service application is entered into a service classification that has been determined. JARDIKNAS-Network of National Education under the Ministry of National Education in terms of information on its web site eligible to be included in the national public service portal.